Climate change and political (in)action: an intergenerational epistemic divide? - Murphy, Susan (My University, 2021)
This paper critically examines the constructed narrative that there is an epistemic intergenerational divide on the topic of climate change, climate science, and the political actions necessary to address the most urgent threats. Analysing publicly available social media data, this paper traces the amplification of youth voice during 2019 and the emergence of this narrative. It compares the dominant messages against 2019 Afrobarometer and Eurobarometer reports which explore voter perspectives on climate change and climate action. Through a process of critical analysis it argues that the constructed narrative of an intergenerational epistemic divide is misleading. It argues that youth voices are subject to structural forms of epistemic injustice and exclusion in climate action deliberations and policy making. However, it finds that voters and older generations are also subject to similar forms of exclusion. Rather than framing this as an epistemic problem, this analysis points to the political-economy climate justice factors influencing the debate. It argues that the real points of contention now rest at the science-policy interface and with what happens when scientific evidence is refracted through dominant political ideologies and translated into policy.
PUBLISHED
Keywords: Intergenerational Justice; Epistemic Justice; Inequality; Science-policy interface; Global political economy; Climate action; International Development; Smart & Sustainable Planet; CLIMATE CHANGE; INEQUALITY; Intergenerational Justice; Political action; Environment and housing; Relationships; Social participation